Review of the 92nd Annual Meeting of the British Association of Dermatologists, 3–5 July 2012, Birmingham, U.K. (21st December 2012) - Lam, M.L.; Patel, A.N.; Ferguson, A.D.
Summary This is a synopsis of the main research and clinical findings presented at the 92nd Annual Meeting of the British Association of Dermatologists, held on 3–5 July 2012 in Birmingham, U.K. The conference highlighted the biological, epidemiological and therapeutic advances that have been made recently in the field of dermatology. This synopsis is a selection of the major findings from the meeting; it is not intended to be a substitute for reading the conference proceedings and related references quoted in this article.